Berbamine and thymoquinone exert protective effects against immune-mediated liver injury via NF-κB dependent pathway - Kathem, Sarmed H.; Abdulsahib, Waleed K.; Zalzala, Munaf H. (Frontiers in Veterinary Science, 2022)
Background Immune-mediated hepatitis is a severe impendence to human health, and no effective treatment is currently available. Therefore, new, safe, low-cost therapies are desperately required. Berbamine (BE), a natural substance obtained primarily from Berberis vulgaris L, is a traditional herbal medicine with several bioactivities, such as antimicrobial and anticancer activities. Thymoquinone (TQ), a phytochemical molecule derived from the Nigella sativa plant's black cumin seeds, has attracted interest owing to itsanti-inflammatory, antioxidant, and anticancer properties. Aim This current study's aims was to examine the protective impacts of BE and TQ in Concanavalin A (ConA)- induced acute liver injury and the action's underlying mechanism. Methods sixty mice of both sexes were used and divided into four groups (each group with six mice) as follows: Group I obtained distilled water (negative control group). Group II received distilled water with a single dose of 0.1 ml ConA (20 mg/kg) on day 4 by retro-orbital route (model group). Groups III and IV received BE (30 mg/kg/day) and TQ (25 mg/kg/day), respectively, by oral gavage for four successive days, with a single dose of ConA (20 mg/kg) on day 4, then all animals were sacrificed after 8 h and prepared for liver and blood collection. Results ConA administration increased the ALT, AST, TNF-α, INFγ, and NF-κB significantly (p < 0.001) in the model group. Both BE and TQ could reduce these parameters significantly (p < 0.001) in groups III and IV, respectively, compared to the model group. Conclusion Both BE and TQ prominently attenuated ConA immune-mediated liver injury. These findings give a remarkable insight into developing a new therapeutic agent for treating hepatitis and other autoimmune diseases.